Efeito residual do pó de basalto e enxofre elementar e resposta da cultura da canola a adubação nitrogenada em cobertura - Santos , Natália Cardoso dos (2022)
Canola and corn are crops of great economic interest and demanding fertility. However, as the most common approach to soil fertilization indicates the use of soluble chemical fertilizers, it is necessary to search for alternative sources of nutrient supply that can complement the fertilization of these crops. In this sense, the use of rock dust is one of the available options. Therefore, the objective of this work was to evaluate the residual effect of basalt dust and elemental sulfur on canola and corn crops, in addition to analyzing the response of these crops to nitrogen fertilization. Two trials were carried out in the same experimental area, adopting the experimental design in randomized blocks with four replications, in a split-plot scheme. In experiment 1, carried out with rapeseed, the plots were constituted by three doses of nitrogen (80, 100 and 120 kg ha-1) using urea as a source of N; the subplots by the presence or absence of the residual effect of basalt dust (12 t ha-1) and the subsubplots by the presence or absence of the residual effect of elemental sulfur (60 kg ha-1). Both basalt powder and elemental sulfur were applied one year before planting the culture. The variables analyzed were the levels of Ca, Mg, K, N and S in the leaf tissue; the crop production components: grains per silique, siliques per plant, mass of one thousand grains and productivity; and soil chemical characterization. The use of basalt powder showed a residual effect after one year of application, with changes in the chemical attributes of the soil through an increase in pH, K and P contents, V% and reduction of potential acidity. The dose of 100 kg ha-1 of N increased the content of this nutrient in the canola plants, while the doses of 80 kg ha-1 and 100 kg ha-1 increased the number of grains per silique of the canola plants. However, crop productivity was not influenced by any of the factors tested. In experiment 2, carried out with corn, the plots were constituted by three doses of organic compost (0; 3 and 6 t ha-1), the subplots by the presence or absence of the residual effect of basalt powder (12 t ha-1) and the subsubplots by the presence or absence of the residual effect of elemental sulfur (60 kg ha-1). Both basalt powder and elemental sulfur were reapplied to the area after the canola crop was harvested. The height and diameter of corn plants were determined, as well as the pH and P, K, Ca, Mg, Cu, Zn, Mn and Fe contents of the soil. The application of 12 t ha-1 of basalt powder resulted in an increase of 78.65% in the P content in the soil. However, due to the prolonged water deficit that occurred during the crop cycle, it was not possible to perform the analysis of leaf tissue nor to determine the productivity of the corn crop.